Notes on 'Lichen'. Issue 6 (3rd July 2019) - Milne, Drew
ABSTRACT: 'Notes on "Lichen"' develops a lichenised homage to Susan Sontag's 'Notes on "Camp"', rewilding Sontag's essay to suggest a poetics of Lichen, a poetics associated symbiotically with the manifestos of Donna Haraway. This Lichen poetics engages with questions of symbiosis and solidarity, mutualism and collective voicing, sketching the turn away from humanist poetics as a critical characteristic of contemporary ecopoetics. From Conceptual Art to contemporary pop, lichen perspectives are gleaned. The attempt is made to rewild earlier conceptual formations, to recycle and repurpose shifts in contemporary taste and their associated politics. New faultlines in contemporary biopolitics are outlined. A chorus of micro-political shifts and transpositions are sketched, revealing emergent and potential turning-points in the rewilding of textual practice.